Mathematical Thinking Styles and the features of Modeling Process - Juhaina Awawdeh Shahbari (Karolinum Press, 2020)
The current study investigated the relationship between students' mathematical thinking style and their modeling processes and routes. Thirty-five eighth-grade students were examined. In the first stage, the students solved questions, and according to their solutions, they were assigned to one of two thinking style groups: visual and analytic. The two groups engaged in three modeling activities. Findings indicated differences in the groups' modeling processes in performing the three activities. The primary differences in the modeling processes were manifested in simplifying, mathematizing, and eliciting a mathematical model. In addition, the analytic thinking group skipped the real-model phase in the three activities, while the visual group built a real model for each activity.